Evaluation of the energy efficiency of combined drying and heat treatment by superheated steam. Issue 12 (10th September 2017) - Park, Yonggun; Han, Yeonjung; Park, Jun-Ho; Chang, Yoon-Seong; Yang, Sang-Yun; Chung, Hyunwoo; Yeo, Hwanmyeong
ABSTRACT: This study compares energy efficiency of a combined drying and heat treatment with that of conventional hot air heat treatment, the theoretical heat consumptions required for each treatment were determined, and the actual heat consumptions for each treatment were measured at a pilot scale. Conventional heat treatment method separately performs kiln-drying and heat treatment for wood with hot air in different equipment. On the contrary, in the combined treatment, the wood is simultaneously dried and heat-treated in the same enclosed space. Because of the time and energy savings, the economic feasibility of combined treatment is much higher than that of conventional heat treatment. Although the theoretical required energy of the combined treatment was similar to that of the two-stage method, the actual energy consumption of combined treatment was less than that of the two-stage method. And, the energy efficiency of the combined treatment was calculated to be two times higher than that of the two-stage method. From the results of this study, decreases in the processing time and energy consumption and increases in the energy efficiency of the combined treatment by superheated steam were quantitatively shown when compared to two-stage method.